Azoxystrobin and Picoxystrobin Lead to Decreased Fitness of Honey Bee Drones (Apis mellifera ligustica) - Wenlong Tong; Lizhu Wang; Bingfang Tao; Huanjing Yao; Huiping Liu; Shaokang Huang; Jianghong Li; Xiaolan Xu; Xinle Duan (Agriculture)
Honey bees (Apis mellifera ligustica) are essential pollinators in both ecosystems and agricultural production. However, their populations are declining due to various factors, including pesticide exposure. Despite their importance, the reproductive castes, particularly drones, remain understudied in terms of pesticide effects. To investigate the effects of azoxystrobin and picoxystrobin on honey bee drones, the drones were exposed to different concentrations of azoxystrobin and picoxystrobin for 14 days; the drone survival, body weight, nutrient content, reproductive organs, and sperm concentration were assessed. Results showed that exposure to both fungicides caused a significant reduction in drone survival rates, with survival rates decreasing progressively as the duration of exposure increased. Compared to the control group, the body weights of drones in all treatment groups were significantly lower on days 7 and 14. Nutrient analysis revealed that low concentrations of azoxystrobin and picoxystrobin increased protein levels, while free fatty acid content decreased significantly in all treatment groups. No significant changes were observed in the total carbohydrate content. Morphological examination of reproductive organs showed that the lengths of the mucus glands and seminal vesicles in drones were significantly shorter in the treatment groups compared to the control group. Furthermore, exposure to azoxystrobin and picoxystrobin resulted in a significant decline in sperm concentration in the drones. These findings indicate that azoxystrobin and picoxystrobin have adverse effects on the health and reproductive capacity of honey bee drones. The present study highlights the need to reassess the risks posed by these fungicides to pollinators, particularly given the critical role of drones in maintaining the genetic diversity and resilience of honey bee colonies. Further research is warranted to elucidate the underlying mechanisms of these effects and explore potential mitigation strategies.